Selected Elements of Personal Income Tax Construction and Their Importance for the Implementation of the Tax Policy (Economic and Political Thought, 2013)
Tax policy is implemented by the tax system that is in force in a particularstate. The construction of taxes that create it makes it possible to implementthat policy to a different extent. The article is aimed at presenting howsome selected elements of the tax construction that the legislator can usedo that. The subject matter of the analysis is the personal income tax. It ismost susceptible to demands serving the assumed fiscal, social and economictargets. All elements of the construction can be used here but the legislatorstresses some of them. They include the range of the tax, the system of taxpreferences and the tax rates. As far as the range is concerned, the legislatortries to apply it to the possibly biggest number of entities so that the subjectsto the tax form a big base. It is also worth highlighting that one of the mostimportant functions of the tax is the regulation of the tax-payers’ income andwealth, and the solutions used for its construction undoubtedly influencethe state of public finance and the level of fiscalism, and the functioning ofa particular economy.